Assessment of Serum Calcium and Phosphorus in Patients with Hypothyroidism: A Hospital-Based Cross-Sectional Study - Sah, Bishesh; Karn, Subhash Lal; Jyoti, Sabita; Sapkota, Suraksha; Shrewastwa, Mukesh Kumar; Regmi, Shishir; Mishra, Akash (Journal of Nepalgunj Medical College, 2025)
Introduction: Hypothyroidism is a clinical status resulting from a deficiency of thyroid hormones or, more rarely, from their impaired activity at the tissue level. Divalent ions, such as calcium and phosphorus are required as cofactors for many enzymes in various metabolic pathways that are directly or indirectly regulated by thyroid hormones. So, a decrease in thyroid hormone can result in mineral disturbances, which lead to an increased incidence of osteoporosis, metabolic syndrome, and cardiovascular diseases.Aims: To assess the alteration of serum calcium and phosphorus in patients with hypothyroidism.Methods: A Hospital-based comparative cross-sectional study was conducted at Nepalgunj Medical College Teaching Hospital, Kohalpur, Nepal. A total of 130 participants, aged 18–60 years, were selected for the study. Out of these, 65 participants diagnosed with hypothyroidism were recruited into the hypothyroid group, and 65 euthyroid, healthy individuals visiting the hospital for routine check-ups were recruited into the euthyroid group. Blood samples were collected over a six-months period, starting from September 27, 2024, and analyzed for free triiodothyronine, free thyroxine, thyroid-stimulating hormone, calcium, and phosphorus to assess the alterations in calcium and phosphorus levels in hypothyroidism.Results: Our study showed that serum calcium levels were significantly decreased, while serum phosphorus levels were significantly increased, in both subclinical hypothyroidism and overt hypothyroidism (p < 0.05) compared to euthyroid individuals. Among the hypothyroid group, serum thyroid-stimulating hormone manifested a significant negative correlation with calcium (r = -0.275, p = 0.02) and a positive correlation with phosphorus (r =0.166, p = 0.186).Conclusion: The present study concludes that hypothyroid participants exhibited serum electrolyte disturbances, such as decreased calcium and increased phosphorus in comparison to euthyroid participants.